Acoustic attenuation analysis of silencers with multi-chamber by using coupling method based on subdomain division technique. (15th January 2017) - Fang, Z.; Ji, Z.L.; Liu, C.Y.
Abstract: For multi-chamber silencers with non-uniform cross-sections at axial direction, the coupling method based on subdomain division technique is proposed. The silencer is divided into several subdomains which impedance matrixes are calculated by using suitable 3-D methods. Combining with the continuity conditions at the interfaces to solve the integral impedance matrix of the silencer, thereby the transmission loss is derived. For the double-chamber silencers, the transmission loss and computational speed results from the proposed method, the numerical mode matching (NMM) method, 3-D finite element (FE) method predictions and experimental measurements are compared, which verifies the accuracy and efficiency.